Trade liberalisation vs. trade remedies: Indonesia's industries struggling from pandemic to endemic transition - Wardah wardah; Chadijah Rizki Lestari; Eka Kurniasari (Geuthèë Institute, Aceh, 2026)
This article analyzes the integration of the law of the WTO with national legislation to protect member states, exemplified by Indonesia's challenges with losses and damage to domestic businesses due to imported goods in the Covid-19 pandemic. The current study seeks the answer of (1) Will Indonesian local industries benefit more from the globalization of the economy? (2) Will they retain the right to restrict or close their markets due to Covid-19 in accordance with WTO agreements? This research employs the normative legal method to provide answers to the posed questions. Researchers have used dynamic data on Indonesia's experiences from the early part of the pandemic to its endemic stage. The results indicate that trade liberalisation is advantageous for countries because it encourages the reduction or elimination of international trade barriers, but free trade can hurt local businesses because of competition from around the world. This means that trade remedies must be implemented to protect the local industry in emergency situations such as during a pandemic transitioning to an endemic state, as these measures can help mitigate the negative impacts of increased foreign competition on local businesses.